India`s look east to act east policy : tracking the opportunities and challenges in the Indo-Pacific - Kaul, Manmohini (ed.) (New Delhi, 2016)
In the 21st Century India shares overlapping interests with countries of Southeast Asia and South Pacific, especially Australia and New Zealand. Much of the new narrative has been shaped by the process of globalisation and the emergence of new regional complexities which compelled India to introspect and overhaul its foreign policy towards the countries to its east. The paradigm shift in India`s policy was based on realism and pragmatism, leading to India`s Look East Policy laying down the conceptual framework for engaging Southeast Asia and later South Pacific. Today, the shaping of Act East Policy, reiterates India`s commitment towards the Indo-Pacific and India`s roadmap of building closer ties with the countries of the region. In this edited volume, the contributors offer fresh insight on issues of common concern, on economic benefits, maritime cooperation and other important topics within the broad framework of Indo-Pacific. These academic reflections are expected to lead to a better understanding of the region and help bridge the gaps in India`s foreign policy towards the countries of Southeast Asia and South Pacific. The authors of this volume are well known scholars and commentators from India and abroad.
Keywords: Foreign policy-India